Increasing Access to Justice for Women, the Poor, and Those Living in Remote Areas : An Indonesian Case Study - World Bank (Washington, DC, 2012)
This briefing note outlines the reform process that produced these notable results, a process that began with targeted grassroots empowerment through engagement with PEKKA, an Indonesian civil society organization supporting women headed households. Formal justice sector institutions and local governments subsequently built on those efforts, with support from international development agencies. The note will outline the range of access-to-justice initiatives involving PEKKA, the Indonesian courts, government partners, and international agencies that have contributed to broader policy reform in the access-to-justice field. It will also describe a series of recent access-to-justice policy developments initiated by Indonesian government institutions and a summary of some key results, highlighting how small-scale pilots and research can provide empirical data on which national agencies can draw to strengthen national policy development and planning processes. The concept of access to justice focuses on two basic objectives of a legal system: 1) that it is accessible to people from all levels of society; and 2) that it is able to provide fair decisions and rules for people from all levels of society, either individually or collectively.